Health, social, and civic society professionals' and volunteers' view on the health among young people in unstable housing situations in the south of Sweden: a qualitative interview study - Elisabeth Mangrio; Maria Afzelius; My Lilja; My Lilja; John Stigmar; Annelie Björkhagen Turesson (Frontiers in Public Health, 2025)
BackgroundStable housing is important for overall health and well-being among young people, and poor-quality housing can trigger multiple diseases, including infections, injuries, chronic diseases, and psychological problems. However, many young people in Sweden struggle with an unstable housing situation. It is therefore important to illuminate how health, social, and civic society professionals and volunteers see the overall health situation for young people (16–27 years) in unstable housing situations.MethodSixteen health, social, and civic society professionals and volunteers, from both municipal and governmental organizations and civic society, were interviewed during 2024 and were reached through convenience and purposive sampling. The data was analyzed with content analysis.ResultsThe results showed that the professionals and volunteers considered that there is a lack of basic necessities, such as food and clothes and often also a place to sleep, among young people in unstable housing situations. They also recounted that the bodies of those young people are weakened as a result of the unstable situation, with its stress and lack of proper care. There are, however, challenges with regard to accessing healthcare and the young people in question are often hesitant to seek care, and inclined to avoid it. Furthermore, the participants mentioned psychosocial challenges, due to loneliness and lack of close contacts with family and friends, and said that people struggling with homelessness tend to suffer from mental illness.ConclusionYoung people in unstable housing situations need support to stabilize them for the future, and in order to work toward a more stable housing situation for these people in the county of Scania, a holistic approach is necessary. This is crucial in view of their overall health, as well as their well-being and life satisfaction.